Benzoxazole phenoxide ligand supported group IV catalysts and their application for the ring‐opening polymerization of rac‐lactide and ε‐caprolactone. (26th April 2021) - Pappuru, Sreenath; Ramkumar, Venkatachalam; Chakraborty, Debashis
Abstract : Monomeric titanium [C48 H62 N2 O6 Ti] (1 ) and zirconium [C48 H62 N2 O6 Zr] (2 ) complexes were synthesized by combining the monoanionic salicylbenzoxazole pro‐ligand 2‐(5‐X‐benzoxazol‐2‐yl)‐6‐R1 ‐4‐R2 ‐phenol, LH (R1, R2, X =  t Bu, t Bu, H, respectively) with Ti(O i Pr)4 or Zr(O i Pr)4 ∙( i PrOH) in a 2:1 stoichiometric ratio. Controlled hydrolysis of the monomeric Ti complex with deionized water yielded a new unusual hexanuclear titanium complex [C126 H144 N6 O21 Ti6 ] (3 ). In addition, the cage formed in this complex 3 was surrounded by all‐oxygen and penta‐coordinated Ti(IV) atoms, which leads to an hexanuclear drum‐shaped Ti complex 3 with a trigonal‐bipyramidal geometry at the metal center. The catalytic activity of these complexes toward ring‐opening polymerization (ROP) of ε ‐caprolactone ( ε‐ CL) and rac ‐lactide ( rac ‐LA) was studied. All these complexes showed moderate to good catalytic activity without using any co‐catalyst additives. Single‐site zirconium alkoxide 2 showed the best catalytic activity and was able to convert 400 units of ε ‐CL or rac ‐LA into the polymer product in high yield (≥90%) within 1 hour under solvent‐free conditions. The obtained polymers showed good control in molecular weight ( M n  = 46.2–6.3 kg/mol) and molecular weight distributions (MWD's = 1.37–1.15). The polymerization of rac ‐LA by 2 yielded iso‐ enriched polylactide ( P m  = 0.60).